Acute inflammatory bowel disease in childbood: a new disease?. Issue 8 (August 1978) - Manuel, P D; Kilby, A; Candy, D; Walker-Smith, J A; Harries, J T
Abstract : Three children aged between 7 and 11 years, after an acute onset of diarrhoea and vomiting, developed protracted diarrhoea and severe loss of weight. None had been abroad. No significant aetiological agent was found. There was evidence of acute inflammatory disease on proximal small intestinal biopsy, and some evidence of more widespread gut involvement–of the rectum in Cases 1 and 2, and the terminal ileum in Cases 2 and 3. The disease resolved spontaneously and without relapse.